PENERAPAN UNIVERSAL PRECAUTION TENTANG UPAYA PENCEGAHAN COVID-19 PADA IBU HAMIL DI BIDAN SURATMI KOTA BATAM - Rahmawati; Silvia Mona; T. Marzila Fahnawal (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Universal Precaution is part of occupational safety and health (K3) which is indispensable in health service activities, universal precautions for pregnant women can be applied by washing hands with soap and running water as often as possible for 20-30 seconds or can use hand sanitizer, keeping a distance and avoiding crowds, wearing masks, practicing coughing and sneezing etiquette, maintaining physical fitness and body immunity, in Indonesia, which is one of the countries affected by the Corona Virus Disease-19 (COVID-19) pandemic with an increasing number of fluctuating sufferers. confirmed incidents (new cases). This COVID-19 pandemic situation requires understanding in efforts to prevent COVID-19 infection. This type of research is quantitative with a descriptive design. Data were obtained through a questionnaire to pregnant women as a sample who visited during the study (accidental sampling). From the results of the study, it is known that most of the respondents (55%) are still lacking in efforts to implement universal precautions for the prevention of COVID-19 by pregnant women. Efforts need to be made to increase the understanding of pregnant women to prevent the transmission of COVID-19 in order to suppress the increasing number of cases